A Note on the Effectiveness of Pairs Trading for Individual Investors - Pizzutilo, Fabio (International Journal of Economics and Financial Issues, 2013)
We investigated the profitability of a simple and easily implementable pairs trading strategy that included trading costs and restrictions to short selling so as to replicate an effective strategy exploitable by an individual investor. Notwithstanding the limitations embodied in our model, pairs trading still works. However, the constraints significantly affect the profitability of the strategy. We found evidence that restrictions to the number of shares that are allowed to be shorted have a relevant impact on the risk profile of the pairs portfolios. Our results support the hypothesis that pairs trading is an equity market neutral investment strategy. Keywords: Pairs trading; market neutral; Italian stock market; trading strategy; statistical arbitrage; short selling; personal finance JEL Classifications: G11